State of California special districts annual report : fiscal year - Kalifornien (1998)
In 2014, the State Controller’s Office transitioned to an open data format for Financial Transactions Reports. View and download comprehensive financial information on the State Controller’s open data website at www.bythenumbers.sco.ca.gov.